System Circuit Analysis of Solar Panel Chicken Egg Incubator - Sulanjari; Wicaksana, Ilyas Rasyid; Simbolon, Kiki Tristiawanti; Setyowati, Agustina Dyah; Rohmat, Nur; Irawan, Ade (Program Studi Teknik Mesin Universitas Pamulang, 2025)
The chicken egg incubator is an innovation in the method of hatching chicken eggs that has higher efficiency and is up-to-date compared to using incubating hens. With this incubator machine, the incubation process of chicken eggs can be controlled and can reach the ideal temperature and humidity for the hatching process of chicken eggs. This research was conducted to find out how much power is used by this chicken egg incubator machine, as well as how long it takes for 300 Wp solar panels to charge a battery with a capacity of 12 V / 80 Ah. The research was conducted to find out the percentage of success of this egg hatching and to calculate how long it takes to reach the BEP (Break Even Point). This chicken egg incubator machine is powered by a 300 Wp solar panel with a 12 V / 80 Ah battery. In the incubator circuit there is a humidifier mist maker component to maintain the incubator humidity at 50%–60%. Lighting uses 2 incandescent lamps with a total power of 50 W, as well as a ventilation fan that turns on when the temperature in the incubator is excessive in order to keep the temperature at 36 ℃–38.5 ℃. The drive motor is set to move for 3 seconds every 3 hours. This chicken egg incubator has a power consumption of 74.55 W with an egg hatching success rate of 86%. This chicken egg incubator takes about 500 days or 1 year and 5 months to reach its BEP (Break Even Point).